Carbon dioxide stripping through water by porous PVDF/montmorillonite hollow fiber mixed matrix membranes in a membrane contactor. Issue 28 (25th February 2015) - DashtArzhandi, M. Rezaei; Ismail, A. F.; Matsuura, T.
Abstract : Hydrophobic montmorillonite-filled polyvinylideneflouride hollow fiber mixed matrix membranes were fabricated via wet phase inversion method to meet the requirements of stripping process through membrane contactor at elevated temperatures. Abstract : Hydrophobic montmorillonite (MMT)-filled polyvinylideneflouride (PVDF) hollow fiber mixed matrix membranes (MMMs) were fabricated by means of wet phase inversion method to meet the requirements of stripping process via membrane contactor at elevated absorbent temperatures. The effects of MMT incorporation into polymer matrix in different loadings (1, 3, 5 wt% of polymer) on the membrane properties and CO2 stripping flux and efficiency were investigated. The incorporation affected the phase inversion process and accelerated the exchange rate of solvent/coagulant, resulting in formation of membranes with longer finger-like pores and higher surface porosity. In addition, the MMMs exhibited higher contact angle and wetting resistance than plain membrane. As a result, physical CO2 stripping flux from water and process efficiency became significantly higher than the plain PVDF hollow fiber with maximum achieved when 5 wt% MMT (coded as M5) was embedded in the polymer. The highest stripping flux of 4.19 × 10 −3 mol m −2 s −1 was achieved by M5 at the tested temperature of 27 °C and the liquid velocity of 2.8 m s −1, which was 38% higher than the plain PVDF hollow fiber at the same operating conditions. A significant stripping performance enhancement was also observed by increasing the temperature of CO2 rich liquid from 27 to 45 and 80 °C. These results suggest that the impregnation of polymeric membranes by inorganic hydrophobic clay particles can be an effective method to improve the morphology and performance of PVDF hollow fibers in CO2 stripping via gas–liquid membrane contactor.